(untitled) (Journal of Engineering, 2011)
Experiments have been conducted to study the local and average heat transfer by mixed convection for hydrodynamically fully developed, thermally developing and fully developed laminar upward air flow in an inclined annulus with adiabatic inner cast iron tube and uniform heated outer aluminum tube with an aspect ratio ( Ω = 0.72) and (L/Dh≈40) for both calming and test sections). A wide range of Reynolds number from 859 to 2024 has been covered, and heat flux has been varied from 159 W/m2 to 812 W/m2 (these values of heat flux and Reynolds number gave Richardson number range from 0.03 to 0.٣٨), with angles of annulus inclination φ =0o (horizontal position), φ =60o (inclined position), and φ =90o (vertical position). The hydrodynamically fully developed condition has been achieved by using aluminum annulus (calming section) has the same dimensions as test section and has connected with it by Teflon piece. The average Nusselt numbers have been correlated with the product of (Richardson number and Reynolds number) and compared with available literature and showed satisfactory agreement. The temperature and local Nusselt number profiles results have revealed that the secondary flows created by natural convection have a significant effect on the heat transfer process.